Contribution of PTEN large rearrangements in Cowden disease: a multiplex amplifiable probe hybridisation (MAPH) screening approach. Issue 10 (2nd May 2008) - Chibon, F; Primois, C; Bressieux, J-M; Lacombe, D; Lok, C; Mauriac, L; Taieb, A; Longy, M
Abstract : Background: Cowden disease is an autosomal dominant syndrome predisposing to cancer and characterised by the occurrence throughout life of hyperplastic, hamartomatous and tumoural lesions affecting various organs. In 60–80% of patients a germline intragenic point mutation of the PTEN tumour suppressor gene is identified, but at least 20% of patients with a well characterised phenotype remain without any identified mutation. Methods: To evaluate the impact of large rearrangement involving the PTEN locus in Cowden disease, we analysed by a multiplex amplifiable probe hybridisation (MAPH) technique 80 unrelated patients referred for diagnosed or suspected Cowden disease, and in whom no PTEN point mutation was detected by a denaturing gradient gel electrophoresis (DGGE) screening. Results: Four heterozygous genomic deletions involving the PTEN gene were identified. These deletions ranged from 13.6–662 kb and are restricted to the PTEN locus in two cases. In the two other cases, the deletion encompassed PTEN and either two or three contiguous genes without any obvious phenotypic effect, except a possible consequence of PAPSS2 haploinsufficiency on bone growth. Sequence analysis of the four deleted alleles did not reveal identity or sequence homology at the two breakpoints of a same allele, suggesting that a mechanism such as non-homologous recombination of the breakage and reunion type could lead to the occurrence of these deletions. Conclusion: Large rearrangements of the PTEN gene can be involved as causing mutation in Cowden disease and MAPH is an efficient screening methodology to detect such a genetic alteration.